2004
DOI: 10.1381/0960892041590845
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Bezoars after Adjustable Gastric Banding

Abstract: Gastric bezoar should be considered after LAGB if the patient complains of persistent high fullness and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Psyllium bezoar causing small bowel obstruction has been reported in elderly populations that chronically use high concentrations of psyllium without adequate water consumption (19,20). Incidents of psyllium bezoar causing esophageal obstruction have also been described in patients who ingest dry psyllium preparations without adequate water (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Psyllium bezoar causing small bowel obstruction has been reported in elderly populations that chronically use high concentrations of psyllium without adequate water consumption (19,20). Incidents of psyllium bezoar causing esophageal obstruction have also been described in patients who ingest dry psyllium preparations without adequate water (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Food bezoars can occur in weight-loss surgery patients, most commonly after gastric banding [89,90]. When they occur in patients seen after RYGB, they most commonly occur within the gastric pouch, although there are numerous case reports demonstrating their development at the jejunojejunal anastomosis [91][92][93].…”
Section: Bezoarsmentioning
confidence: 99%
“…Fox, et al and Deitel, et al have previously reported gastric bezoar formation after vertical banded gastroplasty [3,4]. More recently, bezoars have been reported in bariatric patients after laparoscopic roux-en-y gastric bypass and laparoscopic adjustable gastric band placement [6][7][8]. Although rare, the purpose of this report is to increase awareness of the problem, so clinicians will have a high index of suspicion for its diagnosis when bariatric patients present with obstructive symptoms.…”
Section: Discussionmentioning
confidence: 90%